The Interior «I»: Transdisciplinary Reflections on the Experience of the Numinous - Castro García, Óscar (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
In these times when the scientific ethos describes and delimits scientific explanations with very concrete technical definitions, there exist semantic difficulties not remedied by mystifications whenever one tries to explain boundary themes. A new interdisciplinary connection between the sciences of the mind and the sciences of the spirit appears dealing with the study of mystical phenomena as a fundamental question in posing the problem about the existence of God. The response of neurobiologists center on offering «stimulus-response» explanations, but do not include why stimulus-response occurs because of self-induction. Neither is there any explanation of personal experience, when the individual in a mystic process has different manifestations of his individuality: the ego, self, I, selfhood, etc. They are not the same, and they should be explained in a comparative analysis. This article aims to offer a transdisciplinary program about the study of personal experience as foundation for a study of the «numinous» —following Rudolf Otto— or that which has always been the foundation of mystical experience from the time man became homo religiosus. I will elaborate two of the crucial points of a transdisciplinary program: First, a study of the comparative semantics of the different concepts of I, soul, spirit, and consciousness by using the principal traditional sources, thus allowing the consideration of similarities and differences from ontological and phenomenological perspectives. Second, I will present a brief review of the recent history of neurotheology, offering the explanatory models of different programs of neurobiological study on mystical phenomena. The article concludes with a new epistemological and hermeneutical proposal concerning the question about the personal experience of the numinous within a scientific interdisciplinary framework.